Prospects for the recognition of new subjects of civil rights (legal relations) - Martsenko, Nataliia; Kucharska, Khrystyna (Actual problems of law (Aktual'ni problemi pravoznavstva), 2020)
Relevance of the research topic. The chosen topic is relevant in view of the transformations that are taking place in the modern world and are primarily related to digitalization and active implementation of information technology and artificial intelligence in almost all spheres of human life and society. Moreover, attempts to quickly regulate the use of artificial intelligence at the level of recognition of its legal personality are risky and change the established approaches to the very understanding of civil relations. Therefore, the chosen topic has a social demand of society and does not call into question the feasibility of the study.The purpose of this study is to analyze the composition of civil law and to explore the features of legal personality, which is inherent in the subjects of civil rights. At the same time, it will help to choose and justify one or another way of legal regulation that can be applied to artificial intelligence and robotics.Results of the research. The article analyzes the concept, essence and elements of "legal personality" in the civil law of Ukraine and some foreign countries. Peculiarities of determining the place of artificial intelligence and robots in the law of different countries are studied. The possibility of recognizing artificial intelligence and robots as an object of civil rights (legal relations) is considered. The position on the inexpediency of understanding artificial intelligence and robots as a subject of civil rights is defended, instead, it is proposed to understand artificial intelligence as an object. In addition, the inexpediency of recognizing the legal personality of individual animals is substantiated. Emphasis is placed on the need to strengthen legal guarantees of safe human life given the possible negative impact of modern technology.